The Innovation Path and Strategy of Media Industry Driven by New Quality Productivity - Quan, Meicheng (Journal of Theory and Practice in Economics and Management, 2025)
With the rapid development of information technology, new quality productivity has become an important force to promote innovation in the media industry. This paper aims to explore the impact of new quality productivity on the media industry, analyze the challenges and opportunities currently facing the media industry, and propose corresponding innovation paths and strategies, in order to provide theoretical guidance and practical reference for the sustainable development of the media industry.